Effects of different omega-3 sources, fish oil, krill oil, and green-lipped mussel against cytokine-mediated canine cartilage degradation - Kittisak Buddhachat (2018)
© 2017, The Society for In Vitro Biology. Our purpose was to evaluate the protective effect of three marine omega-3 sources, fish oil (FO), krill oil (KO), and green-lipped mussel (GLM) against cartilage degradation. Canine cartilage explants were stimulated with either 10 ng/mL interleukin-1β (IL-1β) or IL-1β/oncostatin M (10 ng/mL each) and then treated with various concentrations of docosahexaenoic acid (DHA), eicosapentaenoic acid (EPA; 3 and 30 μg/mL), FO, KO, or GLM (250, 500, and 1000 μg/mL) for 28 days. Gene expression was then investigated in primary canine chondrocytes. Our results showed that DHA and EPA as well as omega-3 sources could suppress matrix degradation in cytokine-induced cartilage explants by significantly reducing the increase of sulfated glycosaminoglycans (s-GAGs) and preserving uronic acid and hydroxyproline content (except GLM). These agents were not able to reduce IL-1β-induced IL1B and TNFA expression but were able to down-regulate the expression of the catabolic genes MMP1, MMP3, and MMP13 and up-regulate the anabolic genes AGG and COL2A1; FO and KO were especially effective. Our findings indicated that FO and KO were superior to GLM for their protective effect against proteoglycan and collagen degradation. Hence, FO and KO could serve as promising sources of chondroprotective agents.